Severity of Autism Symptoms and Degree of Attentional Difficulties Predicts Emotional and Behavioral Problems in Children with High-Functioning Autism; a Two-Year Follow-up Study - Andersen, Per N.; Hovik, Kjell T.; Skogli, Erik W.; Øie, Merete G. (Frontiers in Psychology, 2017)
Children with autism often struggle with emotional and behavioral problems (EBP). This study investigated whether level of autism symptoms, attention problems or verbal IQ at baseline can predict EBP two years later in children with High-functioning Autism (HFA). Thirty four participants with HFA and 45 typically developing children (TD) (ages 9-16) were assessed with parent ratings of EBP, autism symptoms, attention problems and a test of verbal IQ. The amount of autism symptoms and degree of attention problems at baseline significantly predicted EBP at follow-up, whereas verbal IQ did not. The findings from this study emphasize the importance of assessing and understanding the consequences of autism symptoms and attention problems when treating EBP in children with HFA. Furthermore, interventions aimed at improving ASD symptoms may positively affect the prevalence of EBP in children with HFA.